Applications of Ion Exchange Materials in Chemical and Food Industries - Inamuddin; Rangreez, Tauseef Ahmad; M. Asiri, Abdullah; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book presents the applications of ion-exchange materials in the chemical and food industries. It includes topics related to the application of ion exchange chromatography in water softening, purification and separation of chemicals, separation and purification of food products and catalysis. This title is a highly valuable source of knowledge on ion-exchange materials and their applications suitable for postgraduate students and researchers but also to industrial R&D specialists in chemistry, chemical, and biochemical technology. Additionally, this book will provide an in-depth knowledge of ion-exchange column and operations suitable for engineers and industrialists.
Use of ion exchange resins in dehydration reactions -- The Application of Ion Exchange Resins in Hydrogenation Reactions -- Use of ion exchange resins in alkylation reactions -- Ion Exchange Resins Catalysed Esterification for the Production of Value Added Petrochemical and Oleochemicals -- Synthesis and control of silver aggregates in ion-exchanged silicate glass by thermal annealing and gamma irradiation -- Use of ion exchange resins in reactive separation -- Chromatographic Reactive Separations -- Ion Exchange Chromatography in Separation and Purification of Beverages -- Ion Exchange Resin Technology in Recovery of Precious and Noble Metals. .
Keywords: Food science; Chemistry, Technical; Inorganic chemistry; Chemistry, Organic; Catalysis; Water; Hydrology; Food Science; Industrial Chemistry; Inorganic Chemistry; Organic Chemistry; Catalysis; Water